Cardiovascular risk factors identified in adult patients receiving Primary Health Care: an integrative review (Revista Contexto & Saúde, 2026)
Objective: To provide a synthesis based on current scientific evidence regarding the factors that trigger cardiovascular diseases and can be identified by healthcare professionals during the care of the adult population in Primary Health Care. Methods: This study consists of an Integrative Literature Review of publications from 2019 to 2024, conducted using BVS, Scopus, Web of Science (WoS), and PubMed databases. The guiding research question was: “What information on the identification of cardiovascular risk factors is necessary to support healthcare professionals in primary care during the delivery of care to adult patients?”. Results: Rayyan software was used to assist in bibliographic management, resulting in a total of 26 articles included in the study. To facilitate data comparison, enhance the understanding of relationships among risk factors, and optimize the analysis, similarity analysis was performed using IRaMuTeQ software. The main risk factors identified were hypertension, diabetes, dyslipidemia, smoking, physical inactivity, obesity, gender, age, and depression. Conclusion: Although cardiovascular disease risk factors are relatively easy to identify, their diagnosis in primary care is often delayed, increasing the risk of adverse events and compromising overall health outcomes. Early detection enables more effective preventive actions and a reduction in morbidity and mortality. Therefore, improving the technical and scientific knowledge of PHC professionals is essential, aligning with the objective of this study to compile evidence on the factors that trigger CVD in the adult population.
Keywords: risk factors; cardiovascular diseases; adult; primary health care; healthcare professionals